"Build It and They Will Come?" - Yuan, Ting; Crowley, Jeannie; Asunka, Stephen; Chae, Hui Soo; Natriello, Gary (International Journal of Advanced Corporate Learning (iJAC), 2010)
With collaborative web technologies such as wikis becoming increasingly popular in the workplace, this case study examined how workers at an education research unit within a graduate school of education perceive the wiki as a platform for communication and collaboration, and the extent to which they actually use a workplace wiki for that purpose. Twenty staff members, for whom a wiki was built, were surveyed, while records of their activities on the wiki over a 6-month period were retrieved and analyzed. Findings reveal that though most of these staff members have positive views towards the wiki as a space that can effectively promote information sharing and collaboration, they are not quite as enthusiastic about engaging the wiki as a medium for their daily collaborative work activities. The possible reasons for this discrepancy are discussed together with recommendations on the strategies similar organizations can adopt to help encourage and maximize wiki usage in the workplace.